Pendidikan Adalah Faktor Penentu Daya Saing Bangsa - Laurensius Dihe Sanga; Yvonne Wangdra (LPPM Universitas Putera Batam, 2023)
The reality of the education system in Indonesia is continually evolving. This article aims to explore the relationship between education and national, even international, competitiveness. Indonesia's national competitiveness has fluctuated over the years. By examining various data, is there an educational factor that determines the nation's competitive position? Through the analysis of various documents and articles, including journals and books, it becomes evident that education is one of the key pillars of a nation's competitiveness. The author gathered material through library research and employed descriptive analysis. The author's findings indicate that education is a critical endeavor for a nation to enhance the quality of its human resources. Therefore, improving the quality and equity of education is essential because it is through education that individuals can become highly competitive and quality-driven individuals.